2013
DOI: 10.1515/jbcpp-2012-0075
|View full text |Cite
|
Sign up to set email alerts
|

Birth month and longevity: birth month of victims of sudden (SCD, ≤1 h) and rapid (RCD, ≤24 h) cardiac deaths

Abstract: Victims of SCD and RCD are unequally distributed according to month of birth. The highest numbers were found for January and March to May. The numbers are higher for the first and second quarter and first trimester in comparison with the months at the end of the year. The lowest numbers of study patients were born in November, December and October. This is in accord with the birth months of American centenarians (100-112 years old) found by colleagues from the University of Chicago. Possible mechanisms for pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…Prior evidence from the US,45 Sweden,67 Germany,89 Austria,1011 Denmark,1011 Australia,10 Lithuania,12 Japan,13 and Spain14 has related seasonal birth month effect to all cause and cardiovascular mortality in later life. Consistent with our current findings, two large longitudinal studies in Sweden (including over six million and four million people, respectively) with 20 years follow-up, reported the lowest cardiovascular mortality among participants born in November 67.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior evidence from the US,45 Sweden,67 Germany,89 Austria,1011 Denmark,1011 Australia,10 Lithuania,12 Japan,13 and Spain14 has related seasonal birth month effect to all cause and cardiovascular mortality in later life. Consistent with our current findings, two large longitudinal studies in Sweden (including over six million and four million people, respectively) with 20 years follow-up, reported the lowest cardiovascular mortality among participants born in November 67.…”
Section: Discussionmentioning
confidence: 99%
“…Later life familial and socioeconomic factors might also be associated with overall and cardiovascular mortality in adulthood 34. However, to our knowledge, none of these previous studies has been able to adequately control for these factors and other potential confounders,4567891011121314 limiting the interpretability of their findings 235…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…After the publication in the Annals of National Academy of Sciences in year 2000 a review article that human longevity is related to month of birth [11] we published four articles proving birth month of different cardiac patients [6]- [8] and patients with oncologic malignancies [9]. In addition some our studies related to Congenital Heart Disease [4] and Down Syndrome [5] in the field of Clinical Cosmobiology showed that many analyzed physical parameters, potentially playing a role in the pathogenesis of the mentioned diseases, are more significant connected at the month of conception (9 months before birth) than these at time of the birth.…”
Section: Discussionmentioning
confidence: 99%
“…[4] [5]. The aim of this study was to: 1) synthesize data related to birth month of patients with such "big killer" diagnoses like Acute Myocardial Infarction (AMI) [6] [7], Rapid and Sudden Cardiac Death (RCD, SCD) [8], and Oncologic Malignancies [9], including 71,965 deaths, and their presumed conception month for each group of pathology and summarized both for all groups of patients, studied in the mentioned studies; 2) compare with analogic data of the literature for a group of centenarians (100 -112 years old) in the USA and; 3) explore the existing differences [10].…”
Section: Background-introductionmentioning
confidence: 99%